Systematic review of the safety and efficacy of antazoline in the treatment of atrial fibrillation. - Raghad Aldulaymi; Ahmad Z. Al Meslamani (GarVal Editorial Ltda., 2022)
Context: In the emergency department, patients with recent-onset atrial fibrillation are typically managed with intravenous antiarrhythmic agents. However, the currently used agents have a low efficacy and safety profile. Antazoline is an antihistaminic agent that has been shown to have a strong antiarrhythmic effect when administered intravenously, facilitating rapid conversion to normal sinus rhythm. Aims: To systematically review the literature on the safety and efficacy of antazoline in the treatment of recent-onset short-duration atrial fibrillation and to compare the clinical efficacy of antazoline to that of other antiarrhythmic agents listed in clinical guidelines. Methods: The study was written in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. A comprehensive search of databases (PubMed, Scopus, ScienceDirect, Web of Sciences, Google Scholar, Clinical trial.gov) for relevant studies in English from inception to 2021 using keywords involving "antazoline" AND other terms such as "antiarrhythmic", "atrial fibrillation", and "arrhythmia". Results: Of the 478 studies identified, 446 were screened, and 7 were included, one of which was a randomized control trial, and the others were observational studies. The majority of studies indicated that antazoline resulted in rapid cardioversion to sinus rhythm. When compared to other pharmacological cardioversion options, antazoline achieved higher cardioversion rates than amiodarone or propafenone and was generally a safer option. Conclusions: Antazoline appears to be an effective pharmacological agent for the rapid cardioversion of short-term atrial fibrillation. More randomized clinical trials, however, should be conducted to strengthen the evidence.